Surgical outcomes of DeBakey type I and type II acute aortic dissection: a propensity score-matched analysis in 599 patients - Lin, Chun-Yu (J Cardiothorac Surg, 2021)
BACKGROUND: The DeBakey classification divides Stanford acute type A aortic dissection (ATAAD) into DeBakey type I (D1) and type II (D2) according to the extent of acute aortic dissection (AAD). This retrospective study aimed to compare the early and late outcomes of D1-AAD and D2-AAD through a propensity score-matched analysis. METHODS: Between January 2009 and April 2020, 599 consecutive patients underwent ATAAD repair at our institution, and were dichotomized into D1 (n = 543; 90.7%) and D2 (n = 56; 9.3%) groups. Propensity scoring was performed with a 1:1 ratio, resulting in a matched cohort of 56 patients per group. The clinical features, postoperative complications, 5-year cumulative survival and freedom from reoperation rates were compared. RESULTS: In the overall cohort, the D1 group had a lower rate of preoperative shock and more aortic arch replacement with longer cardiopulmonary bypass time. The D1 group had a higher in-hospital mortality rate than the D2 group in overall (15.8% vs 5.4%; P = 0.036) and matched cohorts (19.6% vs 5.4%; P = 0.022). For patients that survived to discharge, the D1 and D2 groups demonstrated similar 5-year survival rates in overall (77.0% vs 85.2%; P = 0.378) and matched cohorts (79.1% vs 85.2%; P = 0.425). The 5-year freedom from reoperation rates for D1 and D2 groups were 80.0% and 97.1% in overall cohort (P = 0.011), and 93.6% and 97.1% in matched cohort (P = 0.474), respectively. CONCLUSIONS: Patients with D1-AAD had a higher risk of in-hospital mortality than those with D2-AAD. However, for patients who survived to discharge, the 5-year survival rates were comparable between both groups.